Tingkat Pengetahuan Remaja Pre dan Post Edukasi Pencegahan Risiko Penularan HIV - Aniska Indah Fari; Bangun Dwi Hardika; Veroneka Yosefpa Windahandayani; Muocharla Frisca (Jurnal Ventilator, 2023)
Human Immunodeficiency Virus (HIV) is a virus attacking the human immune system can cause AIDS. Increasing HIV cases and there is transmission in teenager caused by their ignorance about information in risky things. Efforts that can be done is to provide prevention education to teenager. This prevention can be done using ABCDE method (absence of sex, be faithful, condom, drug no/not use drugs, education). It is known different levels of pre and post teenager knowledge about risk prevention education of HIV transmission.Tthis research is a quantitative research and uses a pre-experimental method with one group pretest-posttest design approach. Population in this research is ten grade totaling 524 studnts and sampling 45 respondents. Sampling uses non probability aksidental sampling technique. Education is given through animated videos. Data is analyzed using wilcoxon sign test.The result of this research is majority of respondents aged 16 years totalling 25 (58.1%). Majority of gender is 24 (55.8%) female. Statistical analysis result of wilcoxon sign test is got by p-value of 0.001 (<0.05), so that it can be interpreted that there is different levels of pre and post teenager knowledge about risk prevention education of HIV transmission. This research is expected to give resources about risk prevention of HIV transmission in students and can give motivation to the school in school facilities that can increase knowledge about health.